Architectures and protocols that enable new applications on opticalnetworks. - Veeraraghavan, M.
This article first discusses how advances in networking architectures and protocols can complement advances in optical communications research to increase the overall value of optical networks by enabling more applications. A review of existing optical networking solutions is then provided along with a classification of different types of optical networks. Finally, we show how single-hop and multihop wavelength-routed networks can be used efficiently for fast end-to-end file transfers when these networks are equipped with a hardware-implementable signaling protocol, a routing protocol, and a simple transport protocol
Keywords: WDM; File transfers; Hardware-implementable signaling protocol; Multihop wavelength-routed networks; Networking architectures; Networking protocols; Optical communications research; Optical networking solutions; Optical networks; Routing protocol; Single-hop wavelength-routed networks; Transport protocol; Wavelength-division multiplexing